Planktonic foraminiferal biostratigraphy and assemblage composition across the Cenomanian–Turonian boundary interval at Clot Chevalier (Vocontian Basin, SE France) - F. Falzoni; M.R. Petrizzo; H. C. Jenkyns; A. S. Gale; H. Tsikos (Cretaceous Research, 2016)
The CenomanianeTuronian boundary interval is generally considered a critical time for planktonic foraminifera due to the environmental perturbations associated with Oceanic Anoxic Event 2. However, only the rotaliporids became extinct at the onset of the event, whilst several lineages evolved and/or diversified. This remarkable morphologic plasticity is often overlooked in the literature, partly because a number of stratigraphic sections have only been studied in thin-section due to the degree of lithification of the samples. Improved documentation of the morphological variability of planktonic foraminifera and better defined species concepts are required in order to improve biostratigraphy, particularly as Helvetoglobotruncana helvetica is an unreliable marker for the base of the Turonian. At the same time, detailed study of the planktonic foraminiferal response to OAE 2 demands a more profound knowledge of the assemblage composition. We present new biostratigraphic, taxonomic, and quantitative data for planktonic foraminiferal species from the Clot Chevalier section (Vocontian Basin, SE France), with the aim of (1) providing a detailed biostratigraphic analysis of the section, (2) documenting the morphological plasticity of specimens in this time interval and stabilizing species concepts, and (3) identifying promising markers to improve the resolution of the present biozonation and allow regional correlation. Samples were processed with acetic acid to extract isolated planktonic foraminifera. Assemblages were assigned to the upper Cenomanian Rotalipora cushmani Zone and to the uppermost Cenomanianelowermost Turonian Whiteinella archaeocretacea Zone. Planktonic foraminiferal bioevents and assemblage composition identified at Clot Chevalier are compared with the well-studied Pont d'Issole section located ca. 15 km to the NE, highlighting similarities and differences in the species occurrences that may complicate the stratigraphic correlation between the two sections. The results of our study support the validity ...